2018
DOI: 10.14202/vetworld.2018.530-534
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Leptospira spp. from canine kidney tissues and its association with renal lesions

Abstract: AimThe study aimed to detect the prevalence of Leptospira spp. in kidney tissues collected during necropsy and to establish its association with renal lesions in dogs of Mumbai region.Materials and MethodsKidney tissues from 40 dogs were collected during necropsy after gross examination and then fixed in neutral buffered formalin and Bouin’s fluid for histopathology and histochemistry, respectively. Kidney tissues were also collected for the detection of Leptospira spp. by polymerase chain reaction (PCR) in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…[5][6][7] During the disease's acute phase, dogs typically are presented with an AKI secondary to acute interstitial nephritis. 8 Thirty percent of dogs with acute leptospirosis develop oliguria or anuria. 4 These dogs might die before they reach the recovery stage of kidney function and therefore extracorporeal renal replacement therapy (RRT) is recommended.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] During the disease's acute phase, dogs typically are presented with an AKI secondary to acute interstitial nephritis. 8 Thirty percent of dogs with acute leptospirosis develop oliguria or anuria. 4 These dogs might die before they reach the recovery stage of kidney function and therefore extracorporeal renal replacement therapy (RRT) is recommended.…”
Section: Introductionmentioning
confidence: 99%
“…During the disease's acute phase, dogs typically are presented with an AKI secondary to acute interstitial nephritis 8 . Thirty percent of dogs with acute leptospirosis develop oliguria or anuria 4 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that host-adapted serovars usually cause chronic and subclinical infections, while non-adapted serovars are usually involved in acute, severe, and often fatal cases of leptospirosis [5]. In dogs, host-adapted Leptospira serovars such as Canicola usually cause a subclinical form of leptospirosis, and a carrier state might be established with no apparent clinical signs [20].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, FISH has not been used to investigate Leptospira spp. as a potential cause of kidney disease in either cats or dogs, despite numerous studies using other methods demonstrating their presence within the renal systems of both [ 78 , 79 ]. However, the study of Hutton et al [ 80 ] aimed to use FISH alongside histopathology—specifically, using modified Steiner (MS) and immunohistochemistry (IHC)—and PCR to investigate the presence of Borrelia burgdorferi as a potential cause of Lyme nephritis in dogs.…”
Section: Studies Using Fish To Investigate Disease States In Companio...mentioning
confidence: 99%